(untitled) (CIPEEX, 2025)
Healthy eating is directly related to quality of life. It is the basis for a balanced life, providing energy, vitality and protection against disease. In this sense, regular consumption of fruit, vegetables, whole grains, lean proteins and healthy fats helps to maintain an appropriate weight, improves cardiovascular health, strengthens the immune system and reduces the risk of chronic diseases such as diabetes and hypertension. In turn, non-regular consumption of these groups can compromise health, triggering nutritional deficiencies and increasing the risk of mortality. The aim of this study was to associate the consumption of vegetables with the Quality of Life and Mental Health of civil servants from the Federal Network for Professional, Scientific and Technological Education (FNPSTE). This is a cross-sectional epidemiological study, with a quantitative approach, carried out in November 2022. The sample consisted of 1,563 participants, including teachers and administrative technicians in education (ATE) from all Brazilian regions. An online questionnaire was used to collect sociodemographic data; the WHO Quality of Life Assessment Tool - WHOQOL-100; the Depression, Anxiety and Stress Scale - DASS-21; and the National School Health Survey - PeNSE. The data was analyzed using descriptive statistics, the Chi-square association test and Poisson regression. The measure of effect was the prevalence ratio with its respective 95% confidence intervals (CI). Non-regular consumption is defined as ≤ 5 days a week. All the analyses were carried out in the Statistical Package for the Social Sciences (SPSS) version 23.0, using α = 0.05. Non-regular consumption of vegetables was found in 22.5% of men and 21.3% of women; in married individuals (68.5%); aged ≥ 53 years (78.2%); with MS/ES/EPT level (29.7%); TAE (14.9%); north/northeast region (30.7%); ≥ 31 years of service (88.2%); urban dwellers (22.1%). When associated with Quality of Life, non-regular consumption of vegetables was associated with all domains and the total score (p lt; 0.001). With regard to mental health, non-regular consumption of vegetables was also associated with stress, anxiety and depression (p lt; 0.001). Thus, non-regular consumption of vegetables has a negative impact on general health, impairing quality of life and mental health. Increasing vegetable consumption and adopting healthy dietary alternatives are recommended to promote general well-being.